THE EFFECT OF ADMINISTERING RHIZOME EXTRACT OF CURCUMA (Curcuma Xanthorrhiza Roxb.) AT VARIOUS DOSES ON THE THICKNESS OF VAGINAL EPITHELIUM IN MICE (Mus Musculus) EXPOSED TO MSG - Atmaja, Ria Ramadhani Dwi (Journal of Islamic Pharmacy, 2017)
The usage of Monosodium Glutamate (MSG) as flavour enhancer in food is increasing and has reached alarming condition. Excessive consumption of MSG results in the formation of a number of free radicals in the body and affects the function of hypothalamus. A disturbed hypothalamus results in the decline of estrogen levels, and in turn, this estrogen deficiency causes a decrease in vaginal epithelial proliferation in which epithelial cells become thinner. Giving antioxidants might help to address these problems. One of the plants that is rich in antioxidant and grow in mass in Indonesia is curcuma. This study is aimed at analyzing the effect of giving curcuma extract (Curcuma Xanthorrhiza Roxb.) with varying doses on the thickness of vaginal epithelium in mice that are exposed to MSG. The research design employed in the study is true experimental posttest only control group by using 5 groups, namely: K1 (CMC-Na), K2 (MSG), P1 (MSG + curcuma rhizome extract dose of 0,4mg/gr BW), P2 (MSG + curcuma rhizome extract dose of 0,8mg/gr BW), P3 (MSG + curcuma rhizome extract dose of 1,2mg/gr BW). Vagina of each mouse was taken and studied to measure its epithelial thickness by using a 40x magnification on Olympus micrograph microscope. Data were then analyzed using One Way ANOVA. The results show that there is no significant difference in the thickness of vaginal epithelium in each treatment (Ï-value 0.341). Therefore, it can be concluded that the extract of curcuma rhizome does not have a significant influence on the thickness of vaginal epithelium in mice that are exposed to MSG.Â Keywords : MSG, Curcuma Xanthorrhiza, epithelium, vagina.